Poverty and Artificial Sustainability. A research on the Structure and Dynamics of South America - Gallon, Luciano (Journal of Sociocybernetics, 2013)
In 1950, 113 million people lived in South America, in 2008, 385 million, more than three times. Half of them live in poverty. In 2050, about 485 million people will be living there. Contemporary population dynamics figures on a global average show that by each birth in a rich family there are 38 in poor families. Then it’s necessary to think on new social, ecological and economic systems models to analyze and synthesize their possible sustainability from two perspectives: natural and artificial, and to research on how they are possible and behave. This paper shows the process of building, with the help of first and second order cybernetics tools, a theoretical and practical framework for modeling South America using Systems Dynamics and explores questions such as: Is it possible to reduce poverty following a sustainable path? What is the kind of steady state behind the sustainability ideas? In what sense is it possible to talk of artificial sustainability? What relationship can be found between the scales of space and time of the human perspective and of the sustainability and the dynamics of the new social equilibriums? How such exploration enriches the understanding of social systems and human behavior? What contributions can be offered from such analysis and synthesis to contribute to sustainability? How can the structure and dynamics of South America helps to answer those questions? The obtained results will serve to discover possible inconsistencies and counterintuitive behaviors in traditional conceptions of poverty, development and sustainability.